The Routledge Handbook of Global Sustainability Education and Thinking for the 21st Century (Routledge, 2025)
This Handbook emerges as a pivotal resource in underscoring the important role of sustainability education in catalysing a global shift toward sustainable development. It articulates the need for a profound transformation within institutional leadership and educational frameworks to support the critical global sustainability transition. This Handbook explores sustainability thinking as a critical paradigm shift in confronting the multifaceted challenges of sustainable development. It presents an urgent case for a systemic overhaul in our approach to education in the 21st century, advocating for multidisciplinary education and holistic systems thinking in order to more successfully navigate the complexities of sustainable development. The text discusses the foundational elements of modern sustainability thought and management, including the significance of values, ethics, governance, and the pressing issues of environmental degradation and climate change. It offers an extensive trans-disciplinary overview of sustainability discourse, spanning a broad array of perspectives on sustainability management and education. It provides a comprehensive introduction to the language of sustainability and a detailed examination of sustainability issues, highlighting their implications for education, training, and management development. It addresses urgent global issues such as decarbonisation, resource scarcity, population dynamics, pollution, and land degradation, emphasising the crucial role of educational initiatives in helping to mitigate these challenges. This seminal work has been developed for a diverse audience, including academics, policymakers, students, and educators, serving as a valuable tool for those wanting to comprehend complex global sustainability challenges and the paramount importance of education in supporting global sustainability in the 21st century.